2022
DOI: 10.1093/nar/gkac090
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of small-molecules to recognize G-quadruplexes of c-MYC promoter and telomere and the evaluation of their in vivo antitumor activity against breast cancer

Abstract: DNA G4-structures from human c-MYC promoter and telomere are considered as important drug targets; however, the developing of small-molecule-based fluorescent binding ligands that are highly selective in targeting these G4-structures over other types of nucleic acids is challenging. We herein report a new approach of designing small molecules based on a non-selective thiazole orange scaffold to provide two-directional and multi-site interactions with flanking residues and loops of the G4-motif for better selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 75 publications
(60 reference statements)
0
28
0
Order By: Relevance
“…As for 4c, the result is discussed based on the usual end-stacking favoured by the presence/absence of hindering by the loops, with the addition of some interesting analysis on fluorescence lifetimes and by the careful check of the absence of positive induced dichroic signals (ICD), taken as an indicator of groove binding to G4 [58]. On the other hand, Figure 4d reports the phenylaminoacridine also known as BRACO19, which constitutes a golden reference for G4 binders, to such an extent that it can be used as a fluorescent tag for exchange experiments to prove G4 binding by the competitor [60]. The paper above cited on BRACO19/G4 interaction [59] uses molecular dynamics including explicit solvents to improve a previous theoretical work [61]: both papers emphasise the higher affinity for a G-quartet stacked binding mode.…”
Section: Phenanthrolines and Their Metal Complexesmentioning
confidence: 99%
“…As for 4c, the result is discussed based on the usual end-stacking favoured by the presence/absence of hindering by the loops, with the addition of some interesting analysis on fluorescence lifetimes and by the careful check of the absence of positive induced dichroic signals (ICD), taken as an indicator of groove binding to G4 [58]. On the other hand, Figure 4d reports the phenylaminoacridine also known as BRACO19, which constitutes a golden reference for G4 binders, to such an extent that it can be used as a fluorescent tag for exchange experiments to prove G4 binding by the competitor [60]. The paper above cited on BRACO19/G4 interaction [59] uses molecular dynamics including explicit solvents to improve a previous theoretical work [61]: both papers emphasise the higher affinity for a G-quartet stacked binding mode.…”
Section: Phenanthrolines and Their Metal Complexesmentioning
confidence: 99%
“…Recent studies have indicated the activity of DNA G4 structures as small molecules against breast cancer by targeting the promoter of the human oncogene c-MYC and telomeres [ 47 ]. These small molecules are based on a non-selective thiazole orange scaffold to provide multifaceted interactions with flanking residues [ 47 ].…”
Section: Modification-dependent Alterations In Rna Structurementioning
confidence: 99%
“…Recent studies have indicated the activity of DNA G4 structures as small molecules against breast cancer by targeting the promoter of the human oncogene c-MYC and telomeres [ 47 ]. These small molecules are based on a non-selective thiazole orange scaffold to provide multifaceted interactions with flanking residues [ 47 ]. For example, the transcription of the KRAS oncogene is controlled by a G-rich motif, which is located immediately upstream of the transcriptional start site.…”
Section: Modification-dependent Alterations In Rna Structurementioning
confidence: 99%
“…G-quadruplexes (G4) are widely present throughout the human genome especially in the promoters 36,37 , telomeres 38,39,40 , UTRs 41,42 , intronic regions of genes involved in development, survival and proliferation 43,44 . These four-stranded nucleic acid structures are also increasingly being recognized as regulatory elements for replication, transcription, and other important regulatory roles 45,46,47,48 .…”
Section: Introductionmentioning
confidence: 99%